EFEKTIVITAS PROGRAM ADIWIYATA TERHADAP PERILAKU RAMAH LINGKUNGAN WARGA SEKOLAH DI KOTA DEPOK - Tirza Carol Gracia Tompodung; Siti Badriyah Rushayati; M. Nur Aidi (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Since 2006, Ministry of Environment has promote environmental education, within the framework of a program for education for sustainable development to raise enviromental knowledge and awareness called Adiwiyata. Adiwiyata program runs on a voluntary and formal school in Indonesia. The Adiwiyata school program aims to encourage schools to adopt behaviours that are respectful towards the environment. As a prize of appreciation, the Ministry of Environment gives Adiwiyata awards to a schools that has succeed to met the criteria of green school environment. In 2014, Depok City government proposed nine schools to become National Adiwiyata School, but only six schools has pass the verification of healthy, clean, and beautiful encvironment and was awarded National Adiwiyata thropy and certificate. The study was conducted in order to test the level of knowledge, attitudes and behaviour of the school community that implemented Adiwiyata program, as well as the effectiveness of the program is to improve the knowledge and awaraness through policy insight, implementation of environmental based curriculum, environmental participatory based activity, and sustainable management of supporting facilitie, to support the responsible for the protection and management of environment. The study concluded that Adiwiyata program evident effective to change the green behaviors of school community.